IMPLEMENTASI MANAJEMEN PEMBELAJARAN DI SMA NEGERI 1 KOTA JAYAPURA - Dedi Riyanto; Eko Sulistiono; Diki Kurniawan; Desy A.K. Sembiring (NOKEN : Jurnal Pengelolaan Pendidikan, 2020)
This study aimed to find out the implementation of learning management and supporting and obstacle factors in SMA Negeri 1 Kota Jayapura. This type of research was descriptive qualitative research. The subjects of this study were wali kelas teachers in grades X, XI, and XII, students, principal and vice principals of the curriculum section. Data retrieval techniques were structured interviews, nonpartisan observation guides, and documentation. Data validity tested using triangulation, medium to analyze data using data reduction, data presentation and data verification or inference. The results of research on Implementation of Learning Management in SMA Negeri 1 Kota Jayapura were found that the Implementation of Learning Management which includes planning, implementation and evaluation had been carried out properly based on Kurikulum 2013 guidelines so that the learning program could run well although there were some shortcomings that need to be included in the school. The supporting factors such as schools with educators as Kurikulum 2013 instructors at the city and provincial levels. While the inhibition factor that researchers found is not very significant, namely some teachers when the implementation of Kurikulum 2013 RPP was still carried away with KTSP and class management was still centered on teachers. The 2015-16 year has been a long time in the making, with some teachers overwhelmed by the assessment. Keywords: Maintenance of library space, Library equipment, Library equipment